During the Coronavirus (COVID-19) pandemic, does wearing a mask improve or worsen physical performance? - Santos-Silva, P. R.; D`Andrea Greve, J. M.; Pedrinelli, A. (Revista Brasileira de Medicina do Esporte, 2020)
A mask is a simple device yet it provides high levels of protection. As the virus affects mainly the respiratory tract - the nose, mouth, and lungs - it is highly contagious when people sneeze or cough, or exchange respiratory droplets with other people. This exchange is also promoted when a person is performing physical exercise. Although a mask provides some protection, it does not eliminate the need for social distancing. Around 25% of people infected with the new coronavirus may show no symptoms, yet still transmit the virus. One of the main problems with wearing a mask is that it hinders breathing, with the mask gradually becoming damp, increasing its resistance to air intake. Wearing a mask while performing physical activity requires a period of adaptation, as the flow of air to the lungs is reduced, requiring a reduction in the normal rhythm until the wearer has managed to adapt to it. Vigorous and intense exercise can cause inflammatory activity to increase, and should be minimized in order to protect the im-mune system. Secretory immunoglobulin A (IgA) is an antibody protein used by the immune system to neutralize pathogens, including viruses, and decreases with intense exercise. Exercise is considered intense when it is necessary to breathe through the mouth to eliminate the higher concentrations of CO2, but mouth breathing is associated with infections of the upper respiratory tract. Preference should be given to light to moderate exercise, around three times a week. Wearing a mask, and training in nasal breathing are the best and safest ways to reduce the entry of particles, and should be encouraged during this COVID-19 pandemic. Level of evidence V; Opinion of the specialist.